IMPLEMENTASI PROGRAM PENURUNAN STUNTING DI WILAYAH KERJA PUSKESMAS TUMBUANKABUPATEN SELUMA - Abelia Riski Alifta, Abel; Abelia Riski Alifta; Tamrin Bangsu; Aries Munandar (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
One of the health problems in Indonesia is the high rate of stunting, so the government issued Presidential Regulation Number 72 of 2021. This study aims to describe the implementation of stunting reduction programs in the Working Area of the Tumbuan Health Center, Seluma Regency. The method in this study used descriptive qualitative methods with informants totaling 23 people, determined by purposive sampling techniques. Data collection techniques are observation, interviews and documentation studies. The results of this study show that the implementation of the stunting reduction program has been implemented quite well but not optimally. This is due to several inhibiting factors such as parental parenting, low exclusive breastfeeding, high coverage of pregnant women with chronic lack of energy, and a high percentage of families who smoke. This study concluded that socialization has not been maximally accepted by the community due to community stereotypes towards the government, people who still have not participated in the implementation of the program optimally due to concurrent activities, local customs and others. Monitoring and evaluation is carried out regularly and gradually so that the puskesmas work area can implement stunting reduction programs quite well.